2016
DOI: 10.1038/srep35601
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural characteristics in newly diagnosed Parkinson’s disease: An unbiased whole-brain study

Abstract: Parkinson’s disease (PD) is a debilitating neurodegenerative disorder. Findings on specific white matter (WM) alterations in PD have been inconsistent. We hypothesized that WM changes occur in early PD patients and unbiased whole-brain analysis may provide additional evidence of pathological WM changes in PD. In this study, we examined various indexes of WM microstructure in newly diagnosed PD patients at the whole-brain level. 64 PDs with Hoehn & Yahr stage 1 (HY1PDs), 87 PDs with Hoehn & Yahr stage 2 (HYPD2s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 35 publications
8
61
2
Order By: Relevance
“…Meanwhile, the fact that none of the indices correlated with the UPDRS-III indicates that diffusion alterations do not align with the worsening of motor function, possibly due to the effect of the medication [29]. This observation is in line with the findings of Zhang et al [8] and Wen et al [30], which reported correlations between DTI indices and UPDRS-III in the brain of untreated PD patients and a study by Lenfeldt et al [29], which showed no correlation in the SN and basal ganglia of treated PD patients. In contrast, Kamagata et al [12] revealed significant negative correlations between Vic and ODI in the SNpc and putamen with disease severity in a group of treated PD patients.…”
Section: Discussionsupporting
confidence: 85%
“…Meanwhile, the fact that none of the indices correlated with the UPDRS-III indicates that diffusion alterations do not align with the worsening of motor function, possibly due to the effect of the medication [29]. This observation is in line with the findings of Zhang et al [8] and Wen et al [30], which reported correlations between DTI indices and UPDRS-III in the brain of untreated PD patients and a study by Lenfeldt et al [29], which showed no correlation in the SN and basal ganglia of treated PD patients. In contrast, Kamagata et al [12] revealed significant negative correlations between Vic and ODI in the SNpc and putamen with disease severity in a group of treated PD patients.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the connectometry analysis identified tract‐specific changes in connectivity in the bilateral RLIC, Ex, and PTR, and right SLF, SFO which were not identified by FA. Several studies have utilized connectometry to detect the associations between local WM connectivity patterns and study variables, such as body mass index, chronic stroke, apoA‐1, newly diagnosed Parkinson's disease, and major depression disorder . According to these studies, a connectometry analysis detects a greater number of tract changes correlated with study factors than DTI.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above, previously published studies has investigated connectometry differences in other neurological diseases [24][25][26][27][28][29][30][31][32][33][34], adopting SDF as biomarker of investigation. SDF is a densitybased measurement of diffusion at different orientations and it measures the density of diffusing water, differently from other diffusivity measurements such as Fractional Anisotropy (FA), Apparent Diffusion Coefficient (ADC) and Radial Diffusivity.…”
Section: Discussionmentioning
confidence: 99%
“…The spin distribution function (SDF) is the parameter used for the analysis [23]. This method has been already used for example for the study of Parkinson disease [24][25][26][27][28][29][30], mood disorders [31,32], multiple sclerosis [33] and amyotrophic lateral sclerosis [34].…”
Section: Introductionmentioning
confidence: 99%